Systematic Literature Review of Role of Applied Geomatics in Mapping and Tracking Corona Virus - Mohamad Abdullah, Nazirah; Rambat, Shuib; Mohd Yatim, Mohammad Hafiz; Omar, Abdullah Hisam; Muhamad Yatim, Muhamad Nur (International Journal of Integrated Engineering, 2020)
This review paper focuses on the Role of Applied Geomatics in Mapping of dispersion Corona Virus and sheds the light on the important studies on the topic. It also sheds the light on the tracking Corona Virus literature. This review paper also sheds the light on the definition, conceptualization, and measurement of corona virus mapping and tracking. This review paper has also showed a number of studies that linked the relationship between applied geomatics and the mapping and tracking corona virus. Authors explores the literature about applied geomatics, mapping and tracking from 2009 to end 2019 in order to investigate how these two geomatics techniques were born, how they have developed, which are the shared features and how it play an important role in corona virus the novel pandemic. This systematic review of current literature on applied geomatics and corona virus and provides insight into the initial and proposed framework of integrating geomatics to track and map the corona virus.